Mechanochemical feedback control of dynamin independent endocytosis modulates membrane tension in adherent cells - Joseph Jose Thottacherry (Nature Portfolio, 2018)
Plasma membrane tension is an important factor that regulates many key cellular processes. Here authors show that a specific dynamin-independent endocytic pathway is modulated by changes in tension via the mechano-transducer vinculin.